MicroRNA-10b expression in breast cancer and its clinical association - Zhang, Jianhui; Yang, Jing; Zhang, Xin; Xu, Jia; Sun, Yiyi; Zhang, Purong (PLOS ONE, 2018)
MicroRNAs (miRNAs) are short non-coding RNA molecules that play a significant role in many types of cancers including breast cancer. In the current study, we evaluated the expression levels of microR-10b (miR-10b) in 115 breast cancer patients from Sichuan Cancer Center. Real time reverse transcription-PCR was used to assess miR-10b expression. Clinical data including disease stage, survival status, age, ER/PR/HER2 status, molecular subtypes, tumor size, lymph node status and Ki-67 expression levels were correlated with miR-10b expression levels. Our data showed that the miR-10b expression is correlated with disease stage, living status and tumor sizes. We also found that miR-10b expression levels are higher in the lymph node positive group and the Ki-67 higher scoring group (score > 20). No statistically significant differences were observed based on age or molecular sub-type grouping. In conclusion, miR-10b may be a biomarker for breast cancer and is a potential treatment target.